Collaborative Governance Dalam Penerapan Kampung Madani Sebagai Upaya Penurunan Angka Kemiskinan Di Kota Surabaya - Adzra Ajeng Lestari; Anggraeny Puspaningtyas; Dida Rahmadanik (Public Administration Dept, Faculty of Social and Political Science, 2025)
Surabaya is one of the largest metropolitan areas in Indonesia, almost the same size as Jakarta. Surabaya has experienced rapid infrastructure development and plays an important role in the economy of the surrounding area. This can create new problems for the city of Surabaya, such as the emergence of urban disparities with the presence of slums. In accordance with the Regional Regulation of the City of Surabaya Number 2 of 2024 concerning the Acceleration of Poverty Alleviation in the City of Surabaya, efforts to alleviate poverty in the area must be carried out through various programs. A strategy is carried out in the form of empowering underprivileged communities through the implementation of social programs, for example the Kampung Madani Program which focuses on empowering communities through zakat, infaq, and shodaqoh. This study aims to analyze collaborative governance in the Kampung Madani program in an effort to reduce poverty in the city of Surabaya. In this study, the approach applied is a descriptive qualitative research method. In this study, the objects of this research are 3 Kelurahan in Surabaya, namely Kelurahan Kalirungkut, Kelurahan Tenggilis Mejoyo, and Keputih. The results of this study indicate that the implementation process in the 3 sub-districts that were the objects of this study has not all run optimally. 2 sub-districts have a relatively good collaboration process, but 1 other sub-district has a collaboration process that has not run optimally. Even so, the implementation of the Kampung Madani program has shown a number of small positive achievements.